2015
DOI: 10.1007/s00246-015-1232-3
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic Ventricular Tachycardia, Pregnancy and Teenager: Are They Compatible?

Abstract: Arrhythmias in pregnancy are becoming more common given more available and effective medical, ablation and device treatment options. Several changes associated with pregnancy, increased blood volume, cardiac output, and heart rate secondary to an increased sympathetic state, facilitate more frequent occurrences of arrhythmias throughout the pregnancy and during labor and delivery. We present a case of successful pregnancy in a teenage female with a previous diagnosis of CPVT, followed by a review of the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…This contrasts with our patient who had an implanted ICD, and presented with recurrent episodes of arrhythmia throughout pregnancy that increased during the labor process but were successfully managed with the implementation of a carefully designed management protocol [5]. An earlier case report involved a young woman managed with an ICD and propranolol and propafenone [4]. She had two episodes of admission for maternal arrhythmia secondary to non-adherence with medications.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…This contrasts with our patient who had an implanted ICD, and presented with recurrent episodes of arrhythmia throughout pregnancy that increased during the labor process but were successfully managed with the implementation of a carefully designed management protocol [5]. An earlier case report involved a young woman managed with an ICD and propranolol and propafenone [4]. She had two episodes of admission for maternal arrhythmia secondary to non-adherence with medications.…”
Section: Discussioncontrasting
confidence: 61%
“…Two case reports of CPVT document ICD shocks in pregnancy: one patient undergoing three shocks for appropriate arrhythmias in the first trimester [3]. The other patient underwent a single ICD shock at 26 weeks gestation in the setting of medication noncompliance and subsequently delivered a preterm infant at 30 weeks gestation as a result of preterm prelabor rupture of membranes [4]. A larger retrospective review of 228 pregnancies showed no increased risk of events during or after pregnancy; however, the study was limited by a small patient population further confounded by relatively rare rates of cardiac events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature regarding management and outcomes of catecholaminergic polymorphic VT in pregnant women is scarce. [5][6][7] We present a case of a woman with catecholaminergic polymorphic VT managed in our Heart and Pregnancy Program (Video 1).…”
mentioning
confidence: 99%
“…There is very limited literature regarding the management of patients with CPVT during the peripartum period. Our literature search found only four case reports describing their experience with labor and delivery in patients with polymorphic VT (Ahmed & Phillips, 2016; Burrows, Fox, Biblo, & Roth, 2013; Friday, Moak, Fries, & Iqbal, 2015; Gogle & Kemp, 2018). Given that this is a rare clinical scenario, and there are a lack of guidelines for its management, approaches have varied within all cases reported, including a clinical dilemma about the need to treat or not to treat an asymptomatic patient (Kotschet, Hunter, Kroushev, & Wallace, 2017).…”
Section: Discussionmentioning
confidence: 99%